Selekcija v množičnem komuniciranju - Batagelj, Vladimir (Informatica (Ljubljana), 1978)
The article deals with possibilities of explanation of selection in mass communication processes based on hierarchical clustering of variables and an attempt of automatical selection based on the classification of messages into disjunctive groups.
Keywords: disjunctive groups; disjunktivne grupe; hierarchical clustering; hierarhično razvrščanje; mass communication; množično komuniciranje; selection; selekcija